Synthesis and Lessons Learned from 15 CRP Evaluations - Birner, Regina; Byerlee D. (CGIAR Independent Evaluation Arrangement, 2016)
With the completion of all CGIAR Research Program (CRP) evaluations in 2016, IEA commissioned a Synthesis to build on the evaluative evidence, aiming to draw lessons and highlight patterns across the completed evaluations.